Tanggung Jawab Pejabat Pembuat Akta Tanah (PPAT) terhadap Pendaftaran Hak Tanggungan secara Elektronik: (Studi di Kantor Pertanahan Kota Pekanbaru) - Innegie Sevia; Hasim Purba; Suprayitno Suprayitno (CV Rewang Rencang, 2025)
In the era of public service digitalization, electronic mortgage registration (HT-el) has become an important breakthrough in improving the efficiency and accessibility of land services, but its implementation poses new challenges regarding the legal responsibility of Land Deed Making Officials (PPAT) who are directly involved in the registration process through electronic systems. Juridical empirical research conducted at the Land Office of Pekanbaru City shows that when errors occur in the Mortgage Granting Deed (APHT) or during electronic registration, PPAT is given 5 (five) days to correct the errors, but if they cannot be corrected within that timeframe, the application will be declared null and void. Uncorrected errors can result in the deed losing its authentic power based on court decisions for not meeting formal and material requirements, so that the power of the deed is only as an underhand deed which makes it difficult for the parties entitled to use the deed as valid legal evidence, and to overcome this requires solutions in the form of correcting the deed in APHT and correcting registration in the HT-El application through the process of re-inputting accurate data and re-paying administrative fees.